The role of livestock in food security and environmental protection - Ehui, Simeon K.; Li Pun, H.H.; Mares, V.; Shapiro, Barry I. (International Livestock Research Institute, 1998)
Natural resource degradation and environmental damage are important concerns today. Through the influence of overgrazing, overstocking and feeding of crop residues, livestock have undoubtedly contributed to these processes. All too often, however, allegations about the detrimental impact of livestock on the environment are exaggerated or unfounded. Available empirical evidence does not establish a direct and negative relationship between livestock and the environment in a global context. Nor can the evidence discount the significant contributions that livestock make, in many parts of the world, to aggregate food supply, farm income, human nutrition, and to the sustainability of production systems. Drawing on evidence from past research and the proceedings of a recent global electronic conference on livestock-environment interactions, this paper highlights the vital role played by livestock in promoting productivity and sustainability.